PRAKTIK DESTRUCTIVE FISHING DALAM PERSPEKTIF HUKUM PIDANA INDONESIA: Destructive Fishing Practices In The Perspective Of Indonesian Criminal Law - Taufik, Zahratul’ain; Susilawati, Ika Yuliana (Ganec Swara, 2025)
Destructive fishing is the practice of fishing in ways that damage marine ecosystems, such as the use of explosives and poisons. This activity not only threatens the sustainability of fisheries resources, but also has long-term social and economic impacts on coastal communities. This article examines how Indonesian criminal law responds to this practice, by looking at provisions in the Fisheries Law and the Environment Law, as well as challenges in enforcement. It finds that while criminal law tools are in place, enforcement is limited by structural and cultural constraints. This article recommends an integrated legal approach that includes repressive, restorative and preventive aspects to effectively tackle destructive fishing.